Electricity Markets Instability: Causes of Price Dispersion - Qiang Chen (MDPI AG, 2021)
The creation of a single competitive EU energy market is aimed at establishing a fair price in the integrated market space. However, electricity markets in European countries remain rather fragmented, and the marginal pricing method, which is the basic one used in the market, conditions a persistent price dispersion in the search for market equilibrium. This study examines the dispersion of electricity prices in 40 bidding zones in 26 European countries by means of quartile analysis. The geographic orientation of the markets, direction of electricity flows, and structure of electricity generation are considered as the causes of this dispersion. In the study, the geographical boundaries of the electricity markets are determined using the methods of correlation analysis of prices and transitive closure of commercial electricity flows. This makes it possible to single out highly integrated, moderately integrated, poorly integrated, and non-integrated markets. Using cluster analysis, electricity markets are classified according to the structure of electricity generation and direction of flows, with the identification of five clusters based on the dominant type of generation and three clusters based on the dominant direction of electricity supply. For each factor under investigation, the intragroup price dispersion is established. The results of the study have allowed to build a three-dimensional matrix that provides for determining the directions of changes in electricity prices when moving between its quadrants.